Edukasi Kesehatan Mental Berbasis Fenomena Kecemasan, Kesepian, dan Somatoform melalui Program “Gerakan Sadar Jiwa” di UPTD Puskesmas Marga Jaya - Zahra, Almaira Aura; Putri, Anggi Khoiriyyah; Sarika, Fadia Ayu; Amalya, Layla Putri; Syarif, Marsya Amalia; Abystha, Naswha; Islami, Tiara Putri; Diani, Virza Ratna; Cahyani, Zhika Nur; Rahmi, Kus Hanna (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Mental health is a crucial aspect of individual and community well-being, yet it is often overlooked due to low literacy and persistent stigma. A Community Service Program (KKN) program at the Marga Jaya Community Health Center (UPTD), identified three dominant mental health phenomena in the community: anxiety, loneliness, and somatoform complaints. The anxiety and loneliness phenomena were identified through the "Soul Stories" Voice Box program, which serves as a medium for community emotional expression, while the somatoform symptoms emerged from input from community health center staff. This community service activity aims to increase public understanding and awareness of mental health through psychoeducation based on real needs in the field. The method used was a participatory approach through psychoeducation using leaflets and intervention posters, implemented several times a week with different themes. The results of the activity demonstrated community enthusiasm for involvement, particularly in openly expressing feelings and psychological complaints. This program is considered effective as a promotive and preventive effort for mental health in primary health care.